Should community health workers offer support healthcare services to survivors of sexual violence? a systematic review - Gatuguta, Anne; Katusiime, Barbra; Seeley, Janet; Colombini, Manuela; Mwanzo, Isaac; Devries, Karen (BMC International Health and Human Rights, 2017)
Background: Sexual violence is widespread, yet relatively few survivors receive healthcare or complete treatment. In low and middle-income countries, community health workers (CHWs) have the potential to provide support services to large numbers of survivors. The aim of this review was to document the role of CHWs in sexual violence services. We aimed to: 1) describe existing models of CHWs services including characteristics of CHWs, services delivered and populations served; 2) explore acceptability of CHWs’ services to survivors and feasibility of delivering such services; and 3) document the benefits and challenges of CHW-provided sexual violence services. Methods: Quantitative and qualitative studies reporting on CHWs and other community-level paraprofessional volunteer services for sexual violence were eligible for inclusion. CHWs and sexual violence were defined according to WHO criteria. The review was conducted according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. Quality of included studies was assessed using two quality assessment tools for quantitative, and, the methodology checklist by the National Institute for Health and Clinical Excellence for qualitative studies. Data were extracted and analysed separately for quantitative and qualitative studies and results integrated using a framework approach. Results: Seven studies conducted in six countries (Democratic Republic of Congo, Rwanda, Burma, United States of America, Scotland, Israel) met the inclusion criteria. Different models of care had diverse CHWs roles including awareness creation, identifying, educating and building relationships with survivors, psychosocial support and follow up. Although sociocultural factors may influence CHWs’ performance and willingness of survivors to use their services, studies often did not report on CHWs characteristics. Few studies assessed acceptability of CHWs’ to survivors or feasibility of delivery of services. However, participants mentioned a range of benefits including decreased incidence of violence, CHWs being trusted, approachable, non-judgmental and compassionate. Challenges identified were high workload, confidentiality issues and community norms influencing performance. Conclusions: There is a dearth of research on CHWs services for sexual violence. Findings suggest that involving CHWs may be beneficial, but potential challenges and harms related to CHW-provided services exist. No different models of CHW-provided care have been robustly evaluated for effects on patient outcomes. Further research to establish survivors’ views on these services, and, their effectiveness is desperately needed
Keywords: Sexual violence; Community health workers; Sexual violence healthcare services; Survivors